The Impact of Customer Retention Strategies in the Nepalese GSM Mobile Service Providers: A Case of Pokhara City - Bir, J.B.R. Subarna (Economic Literature, 2018)
The cellular industry of Nepal has grown by many folds with the influx of more mobile network providers in the market creating a hyper competition among themselves. Retaining the existing customers rather than just focusing on the regular market expansion is, therefore, becominginevitable for them to sustain. In this realm, this research carried out with the core objective of identifying and assessing the impact of customer retention strategies adopted by GSM Cellular Network companies, primarily Ncell & Nepal Telecom within the locality of Pokhara, taking a sample of 192 network users as respondents within a survey based research design framework, surfaced some important findings. Five out of the six customer retention strategies so identified: Service quality, customer care services, price, loyalty enhancement programs and communications showed an association with the type of network customer use except for other service facilities which showed no association with the network types. Very few of users from Pokhara were thinking to switch over to other networks. Internet proved to be the most effective marketing strategies than other media. Service Quality and loyalty enhancement programs were found to be the most preferred customer retention strategies by the users of both networks. Economic Literature, Vol. XIII August 2016, page 1-8